History of the Church of Jesus Christ of Latter-day Saints - Roberts, B. H.; Smith, Joseph (Deseret News, 1902)
v. 1-6. Period 1, History of Joseph Smith, the prophet / by himself -- v. 7. Period 2, From the manuscript history of Brigham Young and other original documents.